On the semantic distribution of copular verbs in Tundra Nenets - Mus, Nikolett (Helsingin yliopiston kirjasto, 2022)
It is well known from the literature that sentences with nominal, adjectival, and adverbial predicates in Tundra Nenets involve the use of copular or copula-like verbs (namely ŋa-, me- tara-, xæ- (xăja-)), at least under certain grammatical conditions. Tundra Nenets existential clauses, in addition, contain a copula-like (so-called existential) verb (tăńa-). Even though the copulas are already identified in the language, and the behavior of the various copular elements is well-documented and described, certain distributional aspects of copulas are not indicated in the existing literature. The present paper is devoted to clarify some cases of the (semantic) distribution of copular verbs in Tundra Nenets that have not been affected in detail so far. My goal is (i) to resolve certain seemingly exceptional cases that show difference from the pattern indicated in the literature, and (ii) to add further observastions to the discussion. The topics covered in the present paper are the followings: the use of the copulas ŋa- vs. tara- in clauses with NP/AP predicates; the distribution of the copulas ŋa- vs. me- in locative clauses, and the copula-distribution in locative and existential clauses.